Evaluación bromatológica y organoléptica en quesos frescos de leche cruda procedentes de la parroquia Bilován - Moyano Camacho, Arcesio Eduardo (2025)
This research was carried out in the rural parish of Bilován, San Miguel de Bolívar, Ecuador, with the purpose of evaluating the bromatological, organoleptic, and microbiological characteristics of fresh cheeses made from raw milk, a product of high nutritional and economic relevance in the area. The main issue lies in the limited sanitary infrastructure (only 36.8% of households have access to drinking water and 2.9% to sewage systems), the predominance of artisanal processes, and the risks associated with food safety. For this study, 30 samples of fresh cheeses produced by local farmers were collected. They underwent chemical analyses (pH, moisture, fat, and protein), sensory tests (texture, color, flavor, and aroma), and microbiological examinations to detect Salmonella spp., Escherichia coli, and Listeria monocytogenes. The results revealed that 79% of the samples were contaminated with Salmonella spp. and 21% with E. coli, while Listeria monocytogenes was not detected. Consequently, none of the samples met the food safety standards established by the INEN 9 regulation or the Codex Alimentarius, posing a significant risk to public health. Bromatological analyses identified significant differences in protein, fat, and pH content, while sensory evaluation showed greater consumer acceptance of cheeses with soft texture, mild flavor, and uniform color. This research concluded that the artisanal production of fresh cheeses in Bilován represents a high sanitary risk, linked to the lack of basic services and traditional methods of production. The study recommends strengthening training in Good Manufacturing Practices (GMP), expanding access to technologies such as pasteurizers and refrigeration systems, and promoting public policies and financial support to ensure food safety, consumer health, and the socio-economic sustainability of local producers.